Effects of geographical origin, varietal and farming system on the chemical composition and functional properties of purple grape juices: A review. (June 2016) - Granato, Daniel; Magalhães Carrapeiro, Mariana de; Fogliano, Vincenzo; van Ruth, Saskia M.
Abstract: Background: Grape juice is a beverage derived from Vitis sp genus, mainly V. labrusca, V. vinifera and V. rotundifolia species, in which sales have increased steeply because of the alleged beneficial health effects it exerts when consumed regularly. However, the isolated and interlinked impacts of geographical origin, varietal, and farming system on the juice's chemical composition and functional properties still are not fully comprehended. Scope and approach: This paper aims to assess how the producing region, variety, and farming system of grapes (conventional, organic, and biodynamic) affect the quantitative and qualitatively the chemical composition and the functionality ( in vitro, in vivo ) of juices. Key findings and conclusions: Data have shown that the effects of botanical and geographical origins of purple grapes on the chemical composition (especially phenolic compounds) and functional properties of juices are remarkable. On the other hand, organic and biodynamic grape juices have very similar composition and functional properties in vitro, while organic and conventional are somewhat different. This evidence is in line with in vivo animal studies and human trials on healthy individuals have shown: differences in functional properties, especially antioxidant effects, between organic and conventional grape juices are negligible from the nutritional and biochemical perspectives. Graphical abstract: Highlights: The chemical composition and functional properties of grape juice were reviewed. In vivo and in vitro functional properties of grape juices were analyzed. The effects of geographical and botanical origin on the composition are remarkable. No significant distinction between organic and biodynamic grape juice is observed. It seems that no differences exist regarding the functionality between conventional and organic juices in vivo .